Pengaruh Ketepatan Waktu Pelaporan Laporan Keuangan, Opini Audit, Pergantian Kantor Akuntan Publik dan Perubahan Reputasi Kantor Akuntan Publik terhadap Reaksi Pasar : pada Perusahaan Manufaktur di Bursa Efek Indonesia Tahun 2018-2022 - Angelita Maryumi Lun; Yohanes Demu; Siprianus G. Tefa (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to analyze the effect of timeliness, financial statement reporting, audit opinion, public accounting firm changes and changes in public accounting firm reputation on market reactions in manufacturing companies on the Indonesia Stock Exchange in 2018-2022. This research is a causal research with a quantitative approach and uses secondary data. The data analysis used is Descriptive Statistics, logistic regression analysis and hypothesis testing using IBM SPSS 25 tools. The results showed that the audit opinion variable and changes in the reputation of the Public Accounting Firm (KAP) had a significant effect on abnormal returns, while the timeliness of financial reporting and changes in KAP had no effect. The independent variables in the model are able to explain 25.4% of the variability of abnormal returns, with a model accuracy rate of 71.3%. This shows that information related to the timeliness of financial reporting, audit opinion, change of KAP, and change in KAP reputation is considered an important signal and has a big impact and is a common thing that affects investor decisions and affects stock prices.